(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The success of pedagogical practices heavily relies on the attitudinal dimensions of teacher training. A teacher’s attitude not only shapes their instructional approach but also significantly influences student engagement and learning outcomes. The importance of positive attitudes in teacher training, emphasizing their role in fostering an inclusive, supportive, and innovative learning environment. Attitudinal dimensions such as adaptability, empathy, resilience, and motivation are identified as critical components for effective teaching. The study highlights the interplay between teacher attitudes and pedagogical success, underscoring how training programs can instill and enhance these attributes. By aligning teacher attitudes with professional competencies, educational institutions can achieve sustainable improvements in the quality of teaching and learning. The findings offer actionable insights for designing training programs that prioritize attitudinal development alongside technical skills, thereby enhancing overall pedagogical efficacy.